Role of parental educational level as psychosocial factor in a sample of inpatients with anorexia nervosa and bulimia nervosa - Bevione, Francesco; Martini, Matteo; Longo, Paola; Toppino, Federica; Musetti, Alessandro; Amodeo, Laura; Abbate-Daga, Giovanni; Panero, Matteo (Frontiers in Psychology, 2024)
Introduction Evidence on parental educational level (PEL) as a risk factor for Eating Disorders (EDs) is mixed, and no study has assessed its role in relation to the compliance and outcomes of treatments in EDs. Further, no study differentiated from the educational level of mothers and fathers, nor considered the possible mediation of perfectionism in fostering EDs. Methods A clinical sample of 242 first-ever admitted inpatients with EDs provided information on PEL and completed the following questionnaires: the Eating Disorder Examination Questionnaire (EDE-Q) and the Frost Multidimensional Perfectionism Scale (F-MPS). Clinicians also provided information on the Hamilton Rating Scale for Anxiety (HAM-A) and the Hamilton Rating Scale for Depression (HAM-D) for each participant. Results Individuals with high PEL (whether mothers, fathers, or both parents) showed significantly higher scores on depressive symptoms and lower on parental criticism, were younger, had an earlier age of onset, had fewer years of illness, more were students and employed, and fewer had offspring. Individuals with fathers or both parents with high educational levels suffered more from Anorexia Nervosa rather than Bulimia Nervosa, had a longer length of stay during the current hospitalization, had less dietary restraint, and had higher personal standards. Individuals with mothers with high educational levels showed a lower rate of previous substance or alcohol addiction. Personal standards partially mediated the relationship between higher PEL and lower dietary restraint. Discussion PEL emerged to be a twofold psychosocial risk factor, being associated with higher depressive symptoms and a longer length of stay, but also with a shorter duration of illness and better scholar and working involvement. Higher PEL was related to higher personal standards but not to global perfectionism. Patterns of eating psychopathology emerged based on the high PEL of mothers or fathers.